Metode Weighted Product Pada Pendukung Keputusan Pemilihan Pengurus Himpunan Mahasiswa - Hani Hidayati; Ratih Hafsarah Maharrani; Lutfi Syafirullah; Muhammad Nur Faiz (Journal of Innovation Information Technology and Application (JINITA), 2022)
The Department of Student Association (HMJ) is a student organization at the department level in a university which is an extracurricular activity. HMTI or Informatics Engineering Student Association is one of the HMJ at the Politeknik Negeri Cilacap (PNC). HMTI certainly has a vision and mission, therefore, in order to realize the vision and mission, candidates for management are needed according to the expected criteria. The criteria for determining the decision making of HMTI management include organizational experience, psychology, public speaking, self[1]confidence, having a warning letter (SP) and IPK. This problem was overcome by making a Decision Support System for the recruitment of HMTI management using the weighted product method. This system makes it easy for HMTI coaches and administrators to determine the candidate for the board. Decision Support System (DSS) is an application of information systems aimed at assisting leaders in the decision-making process. This study resulted in recommendations for prospective HMTI PNC administrators who through optimization of the weighted product method with various criteria used had the highest value, so that they became a reference for HMTI supervisors and administrators to choose candidates for the following year